2011
DOI: 10.3996/092010-jfwm-032
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Characterization of Hatchery-Origin Juvenile SteelheadOncorhynchus mykissAdopting Divergent Life-History Strategies

Abstract: Smoltification by juvenile Pacific salmonids has been described as a developmental conflict whereby individuals face several life-history decisions. Smoltification occurs as a result of interactions between organismal condition and environmental cues, although some fish may forgo ocean migration and remain in freshwater streams for some time (residualize). We compared the physiological profiles of steelhead that were actively migrating to the ocean (migratory fish) and those that remained in fresh water (resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…This is not surprising because anadromy should benefit females more than males (Hendry et al 2004). Sex ratios skewed toward females have been observed in adult steelhead populations throughout the species' range, including California, Alaska, the Columbia River basin, and the Kamchatka Peninsula in Russia (Savvaitova et al 1997;Hendry et al 2004;Christie et al 2011;Hanson et al 2011). Female-biased sex ratios in steelhead have been attributed to two separate life history behaviors: the predominance of residualization among males and the tendency of anadromous females to spawn more than once (Savvaitova et al 1997;McMillan et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…This is not surprising because anadromy should benefit females more than males (Hendry et al 2004). Sex ratios skewed toward females have been observed in adult steelhead populations throughout the species' range, including California, Alaska, the Columbia River basin, and the Kamchatka Peninsula in Russia (Savvaitova et al 1997;Hendry et al 2004;Christie et al 2011;Hanson et al 2011). Female-biased sex ratios in steelhead have been attributed to two separate life history behaviors: the predominance of residualization among males and the tendency of anadromous females to spawn more than once (Savvaitova et al 1997;McMillan et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of migratory fish from this location leave the system within 13 days after release from the facility (Hanson et al . ).…”
Section: Methodsmentioning
confidence: 97%
“…This has also been shown for O. mykiss. Hanson et al (2011) found that steelhead smolts released from a hatchery that did not migrate had higher condition factors but were shorter than smolts at the time of release (Table 2). This is relevant because Beakes et al (2010) found in 1 of 2 years that future O. mykiss smolts had higher condition factors than future non-smolts almost a year prior to smolting, but that by NovemberDecember non-smolts had greater condition factors (Table 2), perhaps because smolts became more fusiform in shape as time of smolting approached (Jonsson 1985).…”
Section: Growth Size and Lipid Contentmentioning
confidence: 99%
“…Washington; Hanson et al 2011 Early male maturation in fresh water positively correlated with size and lipid content 9 months prior to the spawning season Oregon; McMillan et al 2012 Females with faster growth and higher lipids matured as residents, while males with faster growth matured as residents; residents had lower metabolic costs.…”
Section: Oregon; Garrett 2013mentioning
confidence: 99%